Comparison between Lactobacillus rhamnosus GG and LuxS-deficient strain in regulating gut barrier function and inflammation in early-weaned piglets - Deng, Zhaoxi; Dai, Jinyan; Wei, Yusen; Ma, Yanfei; Mao, Yingying; Zhang, Jinzhi; Hua, Weidong; Wang, Haifeng (Frontiers in Immunology, 2022)
Background Early weaning-induced stress impairs the intestinal barrier function and adversely affects the health of piglet. Probiotics can be used to prevent and treat various intestinal diseases. Lactobacillus rhamnosus GG (LGG) has an LuxS/AI-2 quorum sensing (QS) system that senses environmental changes through chemical signaling molecules. The aim of the study was to explore whether luxS mutant affects the protective role of LGG in the gut barrier of weaned piglets by comparing the luxS mutant (ΔluxS) with its wild-type (WT). Methods Newborn piglets were orally administered with WT and ΔluxS at dosage of 109 CFU, respectively. Accordingly, newborn piglets in the Con group were orally administered with PBS. Piglets were weaned on day 21 and euthanized on day 24, three days following weaning. Results Supplementation of ΔluxS in advance significantly boosted the relative abundances of healthy microbes (including Catenibacterium, Eubacterium, Lachnospiraceae and Bifidobacterium). WT and ΔluxS maintain intestinal barrier function mainly by promoting intestinal villus to crypt ratio (VCR), occludin protein expression and mucus secretion (P<0.05). Furthermore, LGG reduces pro-inflammatory mediators by inhibiting TLR4 and MAPK signal transduction (P<0.05). Conclusion Both WT and ΔluxS were shown to resist weaning stress by enhancing the intestinal barrier function of piglets. It has to be said that the ability of ΔluxS to maintain intestinal tissue morphology and promote mucus secretion significantly decreased compared with that of WT.